Radiocarbon ages of surface marine sediments at the Southeast Pacific - Dharma Reyes-Macaya; Consuelo Martínez Fontaine; Elisabeth Michel; Yusuke Yokoyama; Mahyar Mohtadi; Gema Marti\'nez-Me\'ndez; Andreas Lücke; Ricardo De Pol-Holz; James C Ingle; Eugenia Gayo; Babette A A Hoogakker; Dierk Hebbeln; et al. (PANGAEA, 2025)
Age constraints were evaluated to enable proxy calibrations using marine sediments from the Southeast Pacific. This dataset includes surface sediment radiocarbon dates from the southeastern Pacific. Surface sediment samples were collected between 1962 and 2010 from between 127 and 3267 meters water depths and latitudes from 22°S to 44°S. The samples were obtained using multicorer (Sonne 156, Sonne 211), gravity core (Sonne 161), and a Petersen grab (USNS Eltanin). The radiocarbon analysis was measured in mixed upper thermocline planktonic foraminifera (MUTPF), mixed shallow infaunal benthic foraminifera (MBF) and monospecific benthic foraminifera. All the Foraminifera selected for radiocarbon analysis were unstained Rose-Bengal foraminifera. Radiocarbon age (14C) span between modern (younger than the calendar year 1950) and 10,480 years.